A simple unit root test consistent against any stationary alternative - Frédérique Bec; Alain Guay (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2020)
This paper proposes t-like unit root tests which are consistent against any stationary alternatives, nonlinear or noncausal ones included. It departs from existing tests in that it uses an unbounded grid set including all possible values taken by the series. In our setup, thanks to the very simple nonlinear stationary alternative specification and the particular choice of the thresholds set, the proposed unit root test contains the standard ADF test as a special case. This, in turn, yields a sufficient condition for consistency against any ergodic stationary alternative. From a Monte-Carlo study, it turns out that the power of our unbounded non adaptive tests, in their average and exponential versions, outperforms existing bounded tests, either adaptive or not. This is illustrated by an application to interest rate spread data.
Keywords: C12; C22; C32; E43; 330; Unit root test; Threshold autoregressive model; Interest rate spread